1986
DOI: 10.4319/lo.1986.31.5.0998
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of inorganic and organic nitrogen by bacteria in marine systems1

Abstract: The relative contribution of various inorganic and organic forms of nitrogen to the nitrogen requirements of picoplankton was examined with 15N tracers. Size fractionation was used to measure uptake by < l-pm size microorganisms, and inhibitors of protein synthesis were used to separate procaryotic from eucaryotic nitrogen uptake, Picoplankton utilized mainly ammonium and amino acids and only negligible amounts of nitrate and urea. Nearly all amino acid uptake was by procaryotes, while both procaryotes and euc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
246
3
1

Year Published

1988
1988
2018
2018

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 368 publications
(261 citation statements)
references
References 34 publications
11
246
3
1
Order By: Relevance
“…The influence of bacterial activity at night cannot be ruled out. It has been demonstrated that a substantial portion of NH4+ uptake by the <2-pm fraction may be due to heterotrophic bacteria (Wheeler and Kirchman 1986) when C is not limiting (Keil and Kirchman 1987). In our study we found a good linear correlation between Chl and N productivity in the <2-pm fraction (r = 0.95, P < O.OOS), providing indirect evidence that phototrophs were dominant.…”
Section: Notesmentioning
confidence: 99%
“…The influence of bacterial activity at night cannot be ruled out. It has been demonstrated that a substantial portion of NH4+ uptake by the <2-pm fraction may be due to heterotrophic bacteria (Wheeler and Kirchman 1986) when C is not limiting (Keil and Kirchman 1987). In our study we found a good linear correlation between Chl and N productivity in the <2-pm fraction (r = 0.95, P < O.OOS), providing indirect evidence that phototrophs were dominant.…”
Section: Notesmentioning
confidence: 99%
“…This work was supported by NSF grant BSR 90-20684. disproportionately large amount of P (Vadstein et al 1988;Glide 1989;Jiirgens and Giide 1990) and N (Wheeler and Kirchman 1986;Kirchman et al 1990) compared to other planktonic organisms. Although these studies support the presumption that bacteria compete favorably for inorganic nutrients, they do not show conclusively that planktonic bacteria grow under conditions of nutrient sufficiency.…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…Bacteria also process on the order of 50% of primary production (Cole et al 1988). Much of this production can be supported by NH4+, and a large fraction of total NH,+ uptake by marine plankl Present address: Texas A&M Univ., % U.S. EPA-GBERL, Gulf Breeze, Florida 3256 1. ton can be attributed to bacteria (Wheeler and Kirchman 1986). NH,+ uptake by bacteria may influence phytoplankton population structure and new production (Kirchman et al 1990).…”
Section: Heterotrophicmentioning
confidence: 99%